2023
DOI: 10.3389/fendo.2023.1099310
|View full text |Cite
|
Sign up to set email alerts
|

Function and mechanism of mesenchymal stem cells in the healing of diabetic foot wounds

Abstract: Diabetes has become a global public health problem. Diabetic foot is one of the most severe complications of diabetes, which often places a heavy economic burden on patients and seriously affects their quality of life. The current conventional treatment for the diabetic foot can only relieve the symptoms or delay the progression of the disease but cannot repair damaged blood vessels and nerves. An increasing number of studies have shown that mesenchymal stem cells (MSCs) can promote angiogenesis and re-epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 266 publications
0
23
0
Order By: Relevance
“…These positive effects were achieved by the secretion of several angiogenic growth factors (e.g. VEGF, FGF, stromal cell‐derived factor‐1, keratinocyte growth factor 2, IGF‐1, placental growth factor and epidermal growth factor) and stem cell differentiation into perivascular cells 132 . The current evidence suggests that both local and systemic ADMSC administration improve diabetic wounds in rodents.…”
Section: Adipose‐derived Mesenchymal Stem Cell Action In Relieving Lo...mentioning
confidence: 74%
“…These positive effects were achieved by the secretion of several angiogenic growth factors (e.g. VEGF, FGF, stromal cell‐derived factor‐1, keratinocyte growth factor 2, IGF‐1, placental growth factor and epidermal growth factor) and stem cell differentiation into perivascular cells 132 . The current evidence suggests that both local and systemic ADMSC administration improve diabetic wounds in rodents.…”
Section: Adipose‐derived Mesenchymal Stem Cell Action In Relieving Lo...mentioning
confidence: 74%
“…It can also promote ulcer healing and is thought to be a vital approach in the management of DFU. 16,61,62 TCC is proven to be significantly superior to common dressing changes and other offloading ways of boosting ulcer healing and minimizing infection. 63,64 HBOT is a promising approach to overcome local hypoxia.…”
Section: Gradementioning
confidence: 99%
“…14,15 MSCs are an efficient method of treating DFU, as evidenced by the growing research that demonstrates their capacity to encourage reepithelialization and angiogenesis, decrease inflammation and the inflammatory process, take part in immunological control, and subsequently heal DFU. 16,17 This review article provides a general snapshot of DFU and discusses in detail MSCs and their role as a novel approach in the treatment of DFU. Moreover, it will take the challenges and general and specific limitations of MSCs into consideration and discuss how to overcome these obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 85% of patients with DM with DFUs have their limbs amputated, which severely affects their quality of life [ 58 ]. Treatment with AD-MSCs accelerates wound healing in mice with DFUs, improves the reepithelialization of injured skin, and increases vascular redistribution in traumatized tissue [ 59 ]. Mechanistically, AD-MSCs restore intraepidermal nerve fiber (IENF) density, reduce apoptosis in neurons and Schwann cells, promote angiogenesis, and reduce chronic inflammation in peripheral nerves [ 59 ].…”
Section: Studies On the Mechanism Of Mscs For The Treatment Of Dm And...mentioning
confidence: 99%
“…Treatment with AD-MSCs accelerates wound healing in mice with DFUs, improves the reepithelialization of injured skin, and increases vascular redistribution in traumatized tissue [ 59 ]. Mechanistically, AD-MSCs restore intraepidermal nerve fiber (IENF) density, reduce apoptosis in neurons and Schwann cells, promote angiogenesis, and reduce chronic inflammation in peripheral nerves [ 59 ]. DFU model rats were treated intravenously with UC-MSCs and showed a significantly higher wound healing rate (45.1% ± 1.8% vs. 26.7% ± 2.1%) on day 8 and a wound healing rate approaching 90% on day 16 [ 60 ].…”
Section: Studies On the Mechanism Of Mscs For The Treatment Of Dm And...mentioning
confidence: 99%